Act Locally, Think Globally: SDGs as Core Content for a 24 Course EAP Program - Gay, Sean Eric Kil Patrick; Tat, Cristina R. (European Journal of Sustainable Development, 2023)
This study will detail how a Sustainable Development Goals-centered English for Academic Purposes (EAP) curriculum was created and implemented at a Japanese university. In 2019, a school of policy studies at a university in Western Japan decided to revamp its undergraduate and graduate curricula to focus on offering most courses in English. Students wishing to pursue courses in International Affairs, Public Policy, and Media Studies would have to be able to write, speak, and attend lectures delivered in English with minimal Japanese language support. To prepare students, the first two years of their undergraduate studies they must enroll into a rigorous EAP program focused on the themes of the Sustainable Development Goals. The program seeks to achieve lateral as well as vertical integration of the four skills Reading, Writing, Listening, and Speaking. This paper will explain the curriculum development process, as well as discuss the successes and failures after one year of implementation. The focus will be on how an increase in socially relevant content, the SDGs, was perceived by students and teachers and how it affected students’ academic development. Keywords: Sustainable Development Goals (SDGs); Curriculum Development; Materials Development; English for Academic Purposes (EAP); Content and Language Integrated Learning (CLIL).